Zero Hunger: A Comparative Review of Food Banks in the UK and India - Nambiar, Ankit Suresh; Thangam, Anandavalli (Archives of Business Research, 2022)
Food banks form an essential aspect of providing food to the underprivileged and those unable to ensure adequate nutrition. Over time, food banks have evolved in many ways, including methods of collection and distribution of food items. This comparative review highlights the significant differences in the organisation and running of food banks in the UK and India. The total food waste in India is larger than in the UK, but comparatively less per head. With over 200 million in India needing support from food banks there is an ever-increasing need to further develop and model food distribution. While the concept of food banks is not new in India, the recruitment of volunteers and attraction of further suitable donors would aid in strengthening the system. Robust data to support this will help countries like India improve the delivery and organisation of their already existing food bank network.